Pengaruh Digital Learning Capability dan Professional Development Support terhadap Kinerja Talenta Dosen dengan Self-Efficacy sebagai Mediasi - Sari Budiarti; Lulu Ulfa Sholihannisa (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
Organizational dynamics and increasing demands for employee loyalty require adaptive leadership approaches and strategic talent management. This study is motivated by the need to understand the roles of Leadership Agility and Talent Identification in enhancing Organizational Commitment, with Employee Engagement and Work Meaningfulness serving as mediating variables. The objective of this research is to analyze both the direct and indirect effects among these constructs to develop a sustainable model of organizational commitment. A quantitative approach was employed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The respondents were employees, selected through purposive sampling. Data were collected using a structured Likert-scale questionnaire and analyzed with SmartPLS 4.0 software. The results reveal that Leadership Agility significantly influences Employee Engagement, while Talent Identification significantly affects Work Meaningfulness. Both mediating variables Employee Engagement and Work Meaningfulness—have a significant impact on Organizational Commitment, confirming their roles as mediators within the structural model. These findings suggest that agile leadership development and effective talent identification systems can foster meaningful work experiences and emotional involvement that directly enhance organizational commitment. The novelty of this study lies in the integration of leadership, talent management, employee work experience, and organizational loyalty into a single structural framework, offering relevant insights for addressing the challenges of modern human resource management.